Tight regulation of ubiquitin-mediated DNA damage response by USP3 preserves the functional integrity of hematopoietic stem cells - Lancini, Cesare; van den Berk, Paul C M; Vissers, Joseph H A; Gargiulo, Gaetano; Song, Ji-Ying; Hulsman, Danielle; Serresi, Michela; Tanger, Ellen; Blom, Marleen; Vens, Conchita; van Lohuizen, Maarten; Jacobs, Heinz; et al. (The Journal of experimental medicine, 2014)
Histone ubiquitination at DNA breaks is required for activation of the DNA damage response (DDR) and DNA repair. How the dynamic removal of this modification by deubiquitinating enzymes (DUBs) impacts genome maintenance in vivo is largely unknown. To address this question, we generated mice deficient for Ub-specific protease 3 (USP3; Usp3Δ/Δ), a histone H2A DUB which negatively regulates ubiquitin-dependent DDR signaling. Notably, USP3 deletion increased the levels of histone ubiquitination in adult tissues, reduced the hematopoietic stem cell (HSC) reserves over time, and shortened animal life span. Mechanistically, our data show that USP3 is important in HSC homeostasis, preserving HSC self-renewal, and repopulation potential in vivo and proliferation in vitro. A defective DDR and unresolved spontaneous DNA damage contribute to cell cycle restriction of Usp3Δ/Δ HSCs. Beyond the hematopoietic system, Usp3Δ/Δ animals spontaneously developed tumors, and primary Usp3Δ/Δ cells failed to preserve chromosomal integrity. These findings broadly support the regulation of chromatin ubiquitination as a key pathway in preserving tissue function through modulation of the response to genotoxic stress.